2013
DOI: 10.3986/ags53103
|View full text |Cite
|
Sign up to set email alerts
|

The spatial structures of Europe

Abstract: Europe is characterized by high regional variety.Evropo zaznamuje pestrost regij. © UNEARTHED OUTDOORS 2013Áron Kincses, Zoltán Nagy, Géza ABSTRACT: Our study aims at describing the spatial structure of Europe with spatial moving average, potential model and the bidimensional regression analysis based on gravity model. Many theoretical and practical works aim at describing the spatial structure of Europe. Partly zones, axes and formations, partly polycentric models appear in the literature. We illustrate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…Also South and eastern Asia reached over 1.4 × 10 12 USD of FDI, which is the leader region in the world (Stoddard and Noy, 2015) and reaches large volumes of international trade (Liu and Ng, 2010). Western Europe may be called a pentagonal system (Kincses et al, 2013) and eastern Asia with all world cities ranked alpha++ and alpha+ (except Dubai). Beijing is very strongly linked with cities of the western Pacific, while Shanghai is closely linked with major global cities including London and New York, rather than China′s capital city.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also South and eastern Asia reached over 1.4 × 10 12 USD of FDI, which is the leader region in the world (Stoddard and Noy, 2015) and reaches large volumes of international trade (Liu and Ng, 2010). Western Europe may be called a pentagonal system (Kincses et al, 2013) and eastern Asia with all world cities ranked alpha++ and alpha+ (except Dubai). Beijing is very strongly linked with cities of the western Pacific, while Shanghai is closely linked with major global cities including London and New York, rather than China′s capital city.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They were also located in the more developed, western part of the region (Kincses, Nagy and Tóth 2013). Figure 1 contains a list of cities home to more than three top-ranked corporations as well as corresponding EECCI index values.…”
Section: Data Sources and Research Methodsmentioning
confidence: 99%
“…Paternalism had deep roots in the so-called Central-Eastern European region (Szücs, 1988;Kincses et al 2013). Within the context of the extension of employment of LED, we concluded that the most important factors were the presence of local heroes.…”
Section: Local Heroesmentioning
confidence: 83%
“…So, the financial crisis escalated into other sectors of the economy, decreased the household real incomes and increased the vulnerability of the whole society. Moreover, the relative regional developmental position of the country worsened in East and Central Europe (Kincses et al 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%